Concept of Public Service in Indonesia (Literacy Analysis of Public Service Implementation in Indonesia) - Jamil Bazarah; Nanik Pujiastuti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Public service is a process of helping others in certain ways that require sensitivity and interpersonal relationships to create satisfaction and success. Every service produces products, both in the form of goods and services (Depdagri, 2004). While the main reference in the implementation of public services (Law No. 25 of 2009 on Public Service), it is explained that public services are activities or series of activities to meet the needs of services in accordance with the laws and regulations for every citizen and resident of goods, services, and / or administrative services provided by public service providers. Poor public service in Indonesia is no secret. Among the state apparatus still seems to complicate the service, so it appears if it can be complicated why it should be facilitated; if it can be slowed down why it should be accelerated; The affairs of the state cannot be finished by us alone, and so on. Such patterns and attitude patterns are certainly not in line.  Public service is a basic function of government, as governments have historically existed and been held to meet the interests and needs of the community or its members. Public service is a product of public bureaucracy received by users and the public at large. Therefore, public services can be defined as a series of activities carried out by public bureaucratic institutions to meet various forms of needs and interests of user communities. The government basically has the basic function of service in accordance with the history of the formation of the state / government with the concept of the state as a night watcher, therefore the government is obliged to serve its people to meet various needs of the community, especially basic human needs such as security, peace, and others. In contrast to various service products in the form of goods that are easy in quality value, in terms of service products in the form of services that are not easy to be in the quality value. However, goods and services are often complementary or complementary to each other, making it difficult to separate from each other. A product in the form of goods is often accompanied by a service, such as car sales business accompanied by service services in the form of warranty and service. Likewise, service services are also often accompanied by the existence of goods services. For example, electricity installation services will certainly be accompanied by the installation of electricity poles and other supporting equipment. Service services are intangible goods, so they do not appear (intangible). Although the form is not visible, but in the process of its implementation can or can be observed and felt, for example a service can be judged to run quickly, slowly, pleasantly, difficult, cheap, or expensive in terms of cost.